2012
DOI: 10.4067/s0717-73482012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Correlación y concordancia entre instrumentos de control del asma en niños

Abstract: Introduction:It has been shown that asthma control and quality of life in children have moderate correlation, however FEV 1 would have only a weak correlation with these control parameters. Our objective was to measure clinical correlation and concordance between parameters of pediatric asthma control in Chilean children. Methods: Study carried out in the Unit of Respiratory Diseases, Roberto del Río Children's Hospital, between November 2009 and May 2010, in a series of persistent asthmatic children between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…The study remained on 56 patients who met the criteria: use of IC regularly, either alone or in combination with long-acting beta 2 agonist, at least 3 months and had none of the conditions (associated pulmonary comorbidity, inadequately performed spirometric tests, or incorrect completion of the C-ACT/ACT questionnaire). In the study sample (56 children) , it was found a predominance of males (58.9%) and a median age of 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) years. There was a statistical association between FEV1 and GINA values (p <0.01), as well as between FEV1 values and those of C-ACT/ACT scores (p <0.01) in relation to controlled and untreated patients.…”
Section: Why Was This Study Done?mentioning
confidence: 76%
See 2 more Smart Citations
“…The study remained on 56 patients who met the criteria: use of IC regularly, either alone or in combination with long-acting beta 2 agonist, at least 3 months and had none of the conditions (associated pulmonary comorbidity, inadequately performed spirometric tests, or incorrect completion of the C-ACT/ACT questionnaire). In the study sample (56 children) , it was found a predominance of males (58.9%) and a median age of 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) years. There was a statistical association between FEV1 and GINA values (p <0.01), as well as between FEV1 values and those of C-ACT/ACT scores (p <0.01) in relation to controlled and untreated patients.…”
Section: Why Was This Study Done?mentioning
confidence: 76%
“…The results found in our study are similar to those of Fuhlbrigge et al 12 , who concluded that FEV 1 is associated with important clinical outcomes in children with asthma, such as symptoms, exacerbations and health care utilization. However, Vidal et al 13 in a study of 88 patients aged 12 to 17 years concluded that FEV 1 would not be an adequate instrument to monitor asthma control in children, since most children with asthma have normal FEV 1 values. Corroborating our study, Yasunori et al 14 analyzed 258 asthmatic children aged 5-11 years and found a positive correlation between C-ACT score and FEV 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuhlbrigge et al in 2006 found similar results, 14 which concluded that FEV 1 is widely associated with important clinical outcomes in children with asthma such as symptoms, exacerbations, and use of health care. Rather, Vidal et al 15 in study with 88 patients between 12 and 17 years of age found that FEV 1 is not an adequate instrument to monitor asthma control in children and adolescents, as much of asthmatic children and adolescents have FEV 1 values within the range of normality.…”
Section: Discussionmentioning
confidence: 99%